2008
DOI: 10.1021/jp806225p
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Phase Stability of Silver Nanocrystals

Abstract: Size dependences of three structural phase transitions, melting, evaporation, and solid-solid transition for silver (Ag) nanocrystals, were investigated with nanothermodynamics. The size-dependent melting temperature T m (r) and evaporation temperature T ev (r) of Ag nanocrystals were determined based on a root-mean-squaredisplacement (rmsd) model. It is found that both T m (r) and T ev (r) decrease with crystal size decreasing for the isolated Ag nanoparticles while T m (r) increases for the Ag nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…This is caused by the enhanced atomic vibrational amplitude with decreasing r associated with the increase of surface/volume ratio. 23,26,38 As shown in Figure 2, our model predictions agree quite well with the simulation results of T m (x, r, d) for Cu x Ni 1−x nanoparticles. In Figure 3, although the simulation results of T m (x, r, d) for Pd 0.5 Pt 0.5 nanowires do not match perfectly our predicted curve, they show the same trend within measurement errors.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is caused by the enhanced atomic vibrational amplitude with decreasing r associated with the increase of surface/volume ratio. 23,26,38 As shown in Figure 2, our model predictions agree quite well with the simulation results of T m (x, r, d) for Cu x Ni 1−x nanoparticles. In Figure 3, although the simulation results of T m (x, r, d) for Pd 0.5 Pt 0.5 nanowires do not match perfectly our predicted curve, they show the same trend within measurement errors.…”
Section: Resultssupporting
confidence: 82%
“…Thus, the T m (x, r, d)/T m (∞) and T eu (x, r, d)/T eu (∞) functions in eq 1 can be rewritten as obeys the thermodynamic law of low dimensional materials, in which the variation of a size-dependent quantity is related to the surface (interface)/volume ratio, or 1/r. [23][24][25][26][27][28][29]38,43 This indicates that surface or interface engineering plays an important role in developing high-performance nanoalloys. Moreover, eq 4 can also be roughly used to compare (a) sizedependent melting temperatures of solid solutions or eutectic alloys in different systems or (b) size-dependent melting temperatures of nanoalloys and those of their constituent metal nanocrystals.…”
Section: Parameters Used In Model Predictionsmentioning
confidence: 99%
“…For all the spherical nano‐Au studied, the initial melting temperatures are lower than that of bulk Au (1337.34 K), decreasing from 1331.28 K for 37.4 nm particles to 889.91 K for 0.9 nm particles. This downward result also was observed in other substances . This is caused by nanoeffects.…”
Section: Resultssupporting
confidence: 75%
“…A large number of research results show that there is a significant effect of size on melting behaviors of nanoparticles . Neyts and Bogaerts researched the melting of nano‐Ni with different particle sizes and found that the melting temperature decreases with the particle size decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…Size-dependent phase stability of silver nanocrystals governing the formation of different Ag polytypes was reported in references [38,44]. Chakraborty et al [39] underlined the importance of the control of growth kinetics prior to the size effect and concluded that the former is enough to obtain any of the three polytypes of Ag.…”
Section: Formation Of Ag-au Nanostructuresmentioning
confidence: 98%